Method for producing hollow polyimide particles, and hollow polyimide particles
In the manufacturing process of the polyimide hollow particles, the chemical imidation reaction is carried out using the emulsion of the inner oil phase and the outer oil phase, and the problems of reducing heat resistance and residual template particles in the prior art are solved, thereby achieving excellent heat resistance and simplification of the production process.
Patent Information
- Application Number
- CN202380051498.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-06
- Filing Date
- 2023-04-27
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art When manufacturing polyimide hollow particles, it is easy to cause the problem of reducing heat resistance, and the use of template particles or high temperature/high pressure conditions is required.
The emulsion of the inner oil phase and the outer oil phase was used for chemical imidation reaction to prepare polyimide hollow particles, and the template particles were not used, and the reaction was carried out below 100°C.
The successful manufacture of polyimide hollow particles with excellent heat resistance avoids the problem of heat resistance reduction caused by template particles residues, simplifies the production process and reduces the requirements of equipment and time.
Smart Images

Figure CN119522249A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing polyimide hollow particles and the polyimide hollow particles, and more particularly to a method for producing polyimide hollow particles having a shell portion and a hollow portion surrounded by the shell portion and the polyimide hollow particles. Background Art
[0002] Polyimide is a chemically and mechanically stable material with excellent heat resistance, solvent resistance, mechanical properties, electrical insulation, etc. Therefore, polyimide can be used for coating materials for electrical insulation parts, molding fillers, electrical / electronic materials, metal / ceramic replacement materials, films, varnishes, adhesives, bulk molding materials, composite materials, etc.
[0003] The polyimide particles obtained by granulating polyimide are given the above-mentioned properties derived from the polyimide as well as the properties derived from the shape and structure thereof. Furthermore, hollow granulation is known as a means of imparting lightness, thermal insulation, etc. to the particles. Therefore, if the polyimide particles are hollow granulated to form polyimide hollow particles, in addition to the above-mentioned properties derived from the polyimide, the particles are also given the properties derived from the hollow structure, and it is expected that the performance in the existing applications will be improved and new applications will be developed.
[0004] Patent document 1 discloses the following method: a polyamic acid solution prepared by dissolving polyamic acid in an organic solvent containing at least 50% of an amide-based solvent is injected into a poor solvent containing a polyacrylate-based high molecular surfactant under specific conditions to prepare a dispersion of polyamic acid microparticles, a pyridine / acetic anhydride mixed solution is added to the prepared dispersion of polyamic acid microparticles, and chemical imidization is performed to prepare a polyimide microparticle dispersion, the organic solvent and the poor solvent are phase-separated for the prepared polyimide microparticle dispersion, the polyimide microparticles are aggregated at the liquid-liquid interface to form polyimide microparticle aggregates, the generated polyimide microparticle aggregates are separated / recovered and then dried, thereby manufacturing polyimide microparticle aggregates.
[0005] However, the polyimide fine particle aggregates obtained by the production method described in Patent Document 1 contain a low-heat-resistant polyacrylate-based high-molecular surfactant used as a dispersant in the fine particle aggregates. In addition, the amount of the dispersant used is large, so there is a problem that the heat resistance that the polyimide can originally exhibit is reduced.
[0006] Patent document 2 discloses a method for producing hollow particles, characterized in that: the shell constituting the hollow particles comprises one or more layers, the outermost layer of the layers is a layer (A) comprising polyimide (a), and the hollow particles have a volume average particle size of 0.1 μm to 1 mm, and the production method comprises the following first to sixth steps.
[0007] First step: a step of producing a polyamic acid solution (S1) containing a polyamic acid and a solvent (s1).
[0008] Second step: a step of dispersing fine particles (A1) containing another material (b) in the polyamic acid solution (S1) to produce a dispersion (D1).
[0009] Step 3: A step of mixing and stirring a dispersion (D2) in which hydrophobic fine particles (A2) are dispersed in a solvent (s2) that does not dissolve the polyamic acid but is compatible with the solvent (s1) with the dispersion (D1) to produce a dispersion (D3) containing precursor particles (A3) of the polyamic acid adsorbed on the surface of the fine particles (A1).
[0010] Step 4: A step of separating and taking out the precursor particles (A3) from the dispersion (D3).
[0011] Step 5: Dispersing the precursor particles (A3) in a hydrophobic solvent (s3) having an SP value of less than 7 and a boiling point greater than the boiling points of the solvent (s1) and the solvent (s2), and carrying out an imidization reaction at a temperature greater than the boiling points of the solvent (s1) and the solvent (s2) and less than the boiling point of the hydrophobic solvent (s3) to obtain a hydrophobic solvent dispersion (D4) of imidized particles (A4).
[0012] Step 6: It is a step of separating, washing and drying from the hydrophobic solvent dispersion (D4) to obtain imidized particles (A4), wherein, when the microparticles (A1) containing other materials (b) are hollow microparticles, the obtained imidized particles (A4) are obtained as target hollow particles, and when the microparticles (A1) are solid microparticles, the obtained imidized particles (A4) are added to an aqueous medium and dispersed, and a solubilizer or decomposition agent for other materials (b) is further added, and the material (b) is removed and washed to obtain the target hollow particles.
[0013] However, the manufacturing method described in patent document 2 is a manufacturing method of hollow particles based on the so-called template method, and the particle size of the obtained particles depends on the particle size of the template particles. In addition, the template particles remain in the hollow part surrounded by the shell portion, and thus, the physical properties of the template particles affect the physical properties of the obtained hollow particles, and there are problems such as reducing the heat resistance that the polyimide can originally embody.
[0014] Patent document 3 discloses a method for producing hollow resin particles with a resin (A) as a shell, characterized in that a solution (E) in which a precursor (A1) of the resin (A) and a phase separation promoter (C) are dissolved in a volatile solvent (B) is suspended in a solvent (D) that is insoluble in the precursor (A1), the resin (A) and the volatile solvent (B) and has a boiling point higher than that of the volatile solvent (B) to obtain a liquid, the obtained liquid is polymerized under pressure to synthesize the resin (A), and then the pressure is released above the boiling point of the volatile solvent (B), and a polyimide resin is disclosed as one of the exemplary compounds of the resin (A).
[0015] However, the production method described in Patent Document 3 is a production method based on severe conditions of high temperature and high pressure, and has problems such as requiring special production equipment and requiring time for heating and cooling, which has poor production efficiency.
[0016] Patent Document 4 discloses hollow particles having a volume average particle size of 0.1 μm to 1 mm, wherein a shell constituting the hollow particles includes one or more layers, and the outermost layer among the layers is a layer (L1) containing a polyimide (a).
[0017] However, the manufacturing method described in Patent Document 4 is a method for manufacturing hollow particles based on the so-called template method, and the particle size of the obtained particles depends on the particle size of the template particles. In addition, the template particles remain in the hollow portion surrounded by the shell portion, and thus, the physical properties of the template particles affect the physical properties of the obtained hollow particles, and there are problems such as reducing the heat resistance that the polyimide can originally exhibit.
[0018] Prior art literature
[0019] Patent Literature
[0020] Patent Document 1: Japanese Patent No. 5429922
[0021] Patent Document 2: Japanese Patent No. 5133107
[0022] Patent Document 3: Japanese Patent No. 4991327
[0023] Patent Document 4: Japanese Patent Application Publication No. 2009-235294 Summary of the invention
[0024] Problem that the invention aims to solve
[0025] The present invention is made to solve the above-mentioned existing problems, and its main purpose is to provide: a method for producing polyimide hollow particles, which method does not require the use of template particles and does not require high temperature / high pressure conditions to produce polyimide hollow particles with excellent heat resistance. In addition, it provides: polyimide hollow particles with excellent heat resistance.
[0026] Solutions for solving problems
[0027] [1] A method for producing hollow polyimide particles according to an embodiment of the present invention is a method for producing hollow polyimide particles having a shell portion and a hollow portion surrounded by the shell portion, the method comprising the following steps: a step of preparing an inner oil phase, wherein the inner oil phase comprises polyamic acid microparticles and a solvent; a step of preparing an outer oil phase, wherein the outer oil phase comprises at least one selected from the group consisting of a compound having a siloxane bond and silica and a hydrocarbon solvent; and a step of performing a chemical imidization reaction in an emulsion prepared from the inner oil phase and the outer oil phase.
[0028] [2] In the method for producing hollow polyimide particles described in [1] above, the compound having a siloxane bond may be polysiloxane.
[0029] [3] In the method for producing hollow polyimide particles described in [1] above, the compound having a siloxane bond may have an azo group.
[0030] [4] In the method for producing hollow polyimide particles described in [1], the silicon dioxide may have a specific surface area of 10 m 2 / g or more hydrophobic silica particles.
[0031] [5] In the method for producing hollow polyimide particles according to any one of [1] to [4], the reaction temperature of the chemical imidization reaction may be 100° C. or lower.
[0032] [6] In the method for producing hollow polyimide particles according to any one of [1] to [5], the solvent contained in the internal oil phase may be an amide solvent.
[0033] [7] In the method for producing hollow polyimide particles according to any one of [1] to [6], the concentration of the polyamic acid fine particles in the emulsion may be 0.1% by weight or more.
[0034] [8] The polyimide hollow particles according to the embodiment of the present invention include a shell portion and a hollow portion surrounded by the shell portion, and the volume average particle size thereof is 0.1 μm to 100 μm.
[0035] [9] In the polyimide hollow particles according to [8] above, the coefficient of variation (CV value) of the particle size of the polyimide hollow particles may be 80% or less.
[0036]
[10] In the polyimide hollow particles described in [8] or [9] above, the 5% thermal weight loss temperature when the temperature of the polyimide hollow particles is increased at 10°C / min in an air atmosphere may be 330°C or higher.
[0037]
[11] In the polyimide hollow particles described in any one of [8] to
[10] above, when the relative dielectric constant of the film F1 formed by mixing 20 parts by weight of the above-mentioned polyimide hollow particles with 80 parts by weight of polyimide is set to Dk1, and the relative dielectric constant of the film F0 formed only by polyimide is set to Dk0, the relative dielectric constant reduction rate calculated by (Dk1 / Dk0)×100(%) can be greater than 20%.
[0038]
[12] The hollow polyimide particles according to any one of [8] to
[11] may be hollow polyimide particles obtained by the production method according to any one of [1] to [7].
[0039] Effects of the Invention
[0040] According to an embodiment of the present invention, a method for producing polyimide hollow particles can be provided, which can produce polyimide hollow particles with excellent heat resistance without using template particles and without high temperature / high pressure conditions. In addition, polyimide hollow particles with excellent heat resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (1) obtained in Example 1.
[0042] Figure 2 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (2) obtained in Example 2.
[0043] Figure 3 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (3) obtained in Example 3.
[0044] Figure 4 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (4) obtained in Example 4.
[0045] Figure 5 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (5) obtained in Example 5.
[0046] Figure 6This is a scanning electron microscope photograph of a particle cross section of the polyimide hollow particles (6) obtained in Example 6.
[0047] Figure 7 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (7) obtained in Example 7.
[0048] Figure 8 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (8) obtained in Example 8.
[0049] Fig. 9 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (9) obtained in Example 9.
[0050] Fig.10 This is a scanning electron micrograph of a particle cross section of the polyimide hollow particles (10) obtained in Example 10. DETAILED DESCRIPTION
[0051] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0052] 《《1. Method for producing polyimide hollow particles》》
[0053] The method for producing hollow polyimide particles according to the embodiment of the present invention is a method for producing hollow polyimide particles having a shell portion and a hollow portion surrounded by the shell portion.
[0054] In the present invention, the term "hollow" means a state in which the interior is filled with a substance other than a resin, such as a gas or a liquid. In order to further exhibit the effects of the present invention, it is preferably a state in which the interior is filled with a gas.
[0055] The shell portion and the hollow portion surrounded by the shell portion may be formed of one hollow region or may be formed of a plurality of hollow regions (porous structure).
[0056] The method for producing hollow polyimide particles according to an embodiment of the present invention includes the following steps: a step of preparing an inner oil phase, wherein the inner oil phase comprises polyamic acid microparticles and a solvent (hereinafter sometimes referred to as step I for convenience); a step of preparing an outer oil phase, wherein the outer oil phase comprises at least one selected from the group consisting of a compound having a siloxane bond and silica and a hydrocarbon solvent (hereinafter sometimes referred to as step II for convenience); and a step of performing a chemical imidization reaction in an emulsion prepared from the inner oil phase and the outer oil phase (hereinafter sometimes referred to as step III for convenience).
[0057] The method for producing hollow polyimide particles according to the embodiment of the present invention may include any appropriate steps other than step I, step II, and step III as long as the effects of the present invention are not impaired.
[0058] The method for producing hollow polyimide particles according to the embodiment of the present invention does not rely on the so-called template method using template particles, and therefore has the advantage that the particle size of the obtained hollow polyimide particles does not rely on the particle size of the template particles. In addition, according to the method for producing hollow polyimide particles according to the embodiment of the present invention, it does not rely on the so-called template method using template particles, and therefore, the template particles do not remain in the hollow portion surrounded by the shell portion, and therefore, has the advantage that the physical properties of the template particles do not affect the physical properties of the obtained hollow polyimide particles, and in particular, has the advantage that the heat resistance that the polyimide can originally reflect can be fully reflected.
[0059] The method for producing polyimide hollow particles according to the embodiment of the present invention has the following advantages: no high temperature / high pressure conditions are required, and therefore no special production equipment for reactions under high temperature / high pressure is required. In addition, factors that reduce production efficiency, such as the time required for heating and cooling, are reduced.
[0060] <1-1. Process I>
[0061] In step I, an internal oil phase containing polyamic acid fine particles and a solvent is prepared.
[0062] The polyamic acid microparticles can be prepared by any appropriate method within the range that does not impair the effects of the present invention. As such a method, for example, a method of mixing and reacting a solution in which tetracarboxylic anhydride is dissolved in a solvent and a solution in which diamine is dissolved in a solvent is mentioned.
[0063] As tetracarboxylic anhydride, any appropriate tetracarboxylic anhydride can be used within the range that does not impair the effect of the present invention. The tetracarboxylic anhydride may be only one kind or two or more kinds. As such tetracarboxylic anhydride, for example: 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, 1,3-bis(2,3-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(2,3-dicarboxyphenoxy)phthalic anhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, Aromatic tetracarboxylic anhydrides such as 2,2',3,3'-biphenyltetracarboxylic anhydride, 2,2',6,6'-biphenyltetracarboxylic anhydride, naphthalene-1,2,4,5-tetracarboxylic anhydride, anthracene-2,3,6,7-tetracarboxylic anhydride, and phenanthrene-1,8,9,10-tetracarboxylic anhydride; aliphatic tetracarboxylic anhydrides such as butane-1,2,3,4-tetracarboxylic anhydride; alicyclic tetracarboxylic anhydrides such as cyclobutane-1,2,3,4-tetracarboxylic anhydride; and heterocyclic tetracarboxylic anhydrides such as pyridine-2,3,5,6-tetracarboxylic anhydride. Among these tetracarboxylic anhydrides, 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA) and pyromellitic anhydride are preferred from the viewpoint of further demonstrating the effects of the present invention.
[0064] As tetracarboxylic anhydride, a part of tetracarboxylic anhydride can be substituted with an acid chloride. If a part of tetracarboxylic anhydride is substituted with an acid chloride, the reaction rate can be increased according to the conditions, or the particle size of the obtained polyamic acid microparticles can be made finer. As the acid chloride, for example, diethylpyromellitate diacyl chloride can be cited.
[0065] As the solvent for dissolving tetracarboxylic anhydride, as long as the tetracarboxylic anhydride is substantially dissolved and the generated polyamic acid microparticles are not dissolved, any appropriate solvent can be used within the scope of not damaging the effect of the present invention. Such a solvent can be only one kind, or it can be more than two kinds. As such a solvent, for example: 2-acetone, 3-pentanone, tetrahydropyrene, epichlorohydrin, acetone, methyl ethyl ketone (MEK), tetrahydrofuran (THF), ethyl acetate, acetanilide, methanol, ethanol, isopropanol, toluene, dimethylbenzene can be cited. In addition, even if it is a solvent for dissolving polyamic acid microparticles such as amide solvents such as N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), if it is adjusted in a manner that the polyamic acid microparticles are not dissolved (such as precipitation) by mixing with the poor solvent of the polyamic acid microparticles as mentioned above, then such a solvent for dissolving polyamic acid microparticles can also be used. In addition, for the purpose of adjusting the molecular weight of the obtained polyamic acid fine particles, water may be used in combination with the above-mentioned solvent as a solvent for dissolving tetracarboxylic anhydride.
[0066] As the concentration of tetracarboxylic anhydride in the solution in which tetracarboxylic anhydride is dissolved in the solvent, any appropriate concentration can be adopted within the range that does not damage the effect of the present invention. From the viewpoint of preparing good spherical polyamic acid microparticles, such a concentration is preferably 0.01 wt % to 20 wt %, more preferably 0.1 wt % to 10 wt %, further preferably 0.3 wt % to 7.0 wt %, and particularly preferably 0.5 wt % to 5.0 wt %.
[0067] For the diamine, any appropriate diamine can be used within the range that does not impair the effect of the present invention. The diamine may be only one kind or two or more kinds. As such diamines, for example, 4,4'-diaminodiphenylmethane (DDM), 4,4'-diaminodiphenyl ether (DPE), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 1,4'-bis(4-aminophenoxy)benzene (TPE-Q), 1,3'-bis(4-aminophenoxy)benzene (TPE-R), o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,4-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-methylene-bis(2-chloroaniline), 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'-diaminodiphenyl sulfide, 2,6'-diaminotoluene, 2 Aromatic diamines such as 1,4-diaminochlorobenzene, 1,2-diaminoanthraquinone, 1,4-diaminoanthraquinone, 3,3'-diaminobenzophenone, 3,4-diaminobenzophenone, 4,4'-diaminobenzophenone, 4,4'-diaminobibenzyl, R(+)-2,2'-diamino-1,1'-binaphthyl, S(+)-2,2'-diamino-1,1'-binaphthyl; aliphatic diamines such as 1,2-diaminomethane, 1,4-diaminobutane, tetramethylenediamine, 1,10-diaminododecane; alicyclic diamines such as 1,4-diaminocyclohexane, 1,2-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 4,4'-diaminodicyclohexylmethane; 3,4-diaminopyridine; 1,4-diamino-2-butanone. Block compounds of diamines can be used as diamines. Among these diamines, 4,4′-diaminodiphenylmethane (DDM), 4,4′-diaminodiphenyl ether (DPE), and 1,3′-bis(4-aminophenoxy)benzene (TPE-R) are preferred from the viewpoint of further exhibiting the effects of the present invention.
[0068] For the purpose of modifying the obtained polyamic acid fine particles, diamine may be used in combination with other amine compounds (monoamine compounds, polyamine compounds, etc.).
[0069] As the solvent for dissolving the diamine, as long as the diamine is substantially dissolved and the generated polyamic acid microparticles are not dissolved, any appropriate solvent can be used within the scope of not damaging the effect of the present invention. Such a solvent can be only one kind, or it can be more than two kinds. As such a solvent, for example: 2-acetone, 3-pentanone, tetrahydropyrene, epichlorohydrin, acetone, methyl ethyl ketone (MEK), tetrahydrofuran (THF), ethyl acetate, acetanilide, methanol, ethanol, isopropanol, toluene, dimethylbenzene can be cited. In addition, even if it is a solvent for dissolving the polyamic acid microparticles such as amide solvents such as N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), if it is adjusted in a manner that the polyamic acid microparticles are not dissolved (such as precipitation) by mixing with the poor solvent of the polyamic acid microparticles as mentioned above, then such a solvent for dissolving the polyamic acid microparticles can also be used.
[0070] The concentration of the diamine in the solution in which the diamine is dissolved in the solvent can be any appropriate concentration within the range that does not impair the effect of the present invention. From the viewpoint of preparing good spherical polyamic acid microparticles, such a concentration is preferably 0.01% by weight to 20% by weight, more preferably 0.1% by weight to 10% by weight, further preferably 0.3% by weight to 7.0% by weight, and particularly preferably 0.5% by weight to 5.0% by weight.
[0071] As a method for mixing and reacting a solution of tetracarboxylic anhydride dissolved in a solvent and a solution of diamine dissolved in a solvent, any appropriate method can be adopted within the scope that does not impair the effect of the present invention. From the viewpoint of being able to further reflect the effect of the present invention, as a method for mixing and reacting a solution of tetracarboxylic anhydride dissolved in a solvent and a solution of diamine dissolved in a solvent, a method of stirring using ultrasound is more preferred. By stirring based on ultrasound, it is possible to achieve a miniaturization of about 50% in terms of average particle size compared to the usual stirring method. Stirring based on ultrasound can adopt any appropriate ultrasonic device and conditions such as an ultrasonic emulsifier such as an ultrasonic homogenizer (manufactured by Branson, etc.). The frequency of the ultrasound wave can be appropriately set according to the desired particle size, etc., and is usually about 10kHz to 100kHz, preferably 15kHz to 45kHz.
[0072] As the temperature at which the solution of tetracarboxylic anhydride dissolved in a solvent and the solution of diamine dissolved in a solvent are mixed and reacted, any appropriate temperature can be adopted within the range that does not impair the effect of the present invention. From the viewpoint of preparing good spherical polyamic acid microparticles, such a temperature is preferably 0°C to 130°C, more preferably 5°C to 80°C, further preferably 10°C to 50°C, particularly preferably 15°C to 40°C, and most preferably 20°C to 30°C.
[0073] As the time for mixing and reacting a solution of tetracarboxylic anhydride dissolved in a solvent and a solution of diamine dissolved in a solvent, any appropriate time can be adopted within the range that does not impair the effect of the present invention. From the viewpoint of preparing good spherical polyamic acid microparticles, such time is preferably 10 seconds to 24 hours, more preferably 10 seconds to 12 hours, further preferably 10 seconds to 6 hours, and particularly preferably 10 seconds to 1 hour.
[0074] The molar ratio of tetracarboxylic anhydride to diamine may be any appropriate molar ratio within a range that does not impair the effects of the present invention. From the viewpoint of preparing good spherical polyamic acid fine particles, such a molar ratio is preferably 1:0.5 to 1:1.5, more preferably 1:0.8 to 1:1.2, and even more preferably 1:0.9 to 1:1.1.
[0075] According to the method of mixing and reacting a solution of tetracarboxylic anhydride dissolved in a solvent and a solution of diamine dissolved in a solvent, polyamic acid microparticles are typically precipitated as microparticles in the solvent. Therefore, the polyamic acid microparticles precipitated in the solvent can be separated by solid-liquid separation and isolated by any appropriate method, washed by any appropriate method as needed, and dried by any appropriate method as needed to obtain.
[0076] As a method for solid-liquid separation, any appropriate method can be adopted within a range that does not impair the effects of the present invention. As such a method for solid-liquid separation, for example, centrifugal separation can be mentioned.
[0077] As a solvent for preparing the inner oil phase, any appropriate solvent can be used within the scope that does not impair the effect of the present invention. Such a solvent may be only one kind or may be two or more kinds. From the viewpoint of further reflecting the effect of the present invention, as a solvent for preparing the inner oil phase, an amide solvent can be preferably mentioned. As an amide solvent, for example: N,N-dimethylformamide (DMF), N,N-dimethylacetamide, N-methyl-2-pyrrolidone (NMP), 1,3-dimethyl-2-imidazolidinone, acetanilide can be mentioned.
[0078] The inner oil phase may contain any other appropriate components as long as it contains polyamic acid microparticles and a solvent, within the range that does not impair the effect of the present invention. From the viewpoint of further embodying the effect of the present invention, the total content ratio of the polyamic acid microparticles and the solvent in the inner oil phase is preferably 80% by weight to 100% by weight, more preferably 90% by weight to 100% by weight, further preferably 95% by weight to 100% by weight, and particularly preferably 98% by weight to 100% by weight.
[0079] The internal oil phase may contain a non-crosslinking polymer as the above-mentioned other component, and the non-crosslinking polymer is at least one selected from the group consisting of polyolefins, styrene polymers, (meth) acrylic polymers, styrene-(meth) acrylic polymers, polycarbonates, and styrene-maleic anhydride copolymers. Such non-crosslinking polymers may be only one kind or two or more kinds.
[0080] In order to further exhibit the effects of the present invention, the content of the non-crosslinked polymer in the internal oil phase is preferably 0% to 20% by weight, more preferably 0% to 10% by weight, further preferably 0% to 5% by weight, and particularly preferably 0% to 2% by weight.
[0081] In order to further demonstrate the effects of the present invention, the internal oil phase is preferably prepared by dissolving polyamic acid microparticles in a solvent. When the internal oil phase contains a non-crosslinked polymer, the internal oil phase is preferably prepared by dissolving polyamic acid microparticles and the non-crosslinked polymer in a solvent.
[0082] As the concentration of the polyamic acid microparticles in the internal oil phase, any appropriate concentration can be adopted within the range that does not impair the effect of the present invention. From the viewpoint of being able to further embody the effect of the present invention, such a concentration is preferably 0.1 wt % to 50 wt %, more preferably 1 wt % to 40 wt %, further preferably 5 wt % to 35 wt %, and particularly preferably 10 wt % to 30 wt %.
[0083] 《1-2. Process II》
[0084] In step II, an external oil phase is prepared, and the external oil phase contains at least one selected from the group consisting of a compound having a siloxane bond and silicon dioxide and a hydrocarbon solvent. At least one selected from the group consisting of a compound having a siloxane bond and silicon dioxide preferably functions as a dispersant. The compound having a siloxane bond may be only one or more. The silicon dioxide may be only one or more.
[0085] By using at least one selected from the group consisting of a compound having a siloxane bond and silicon dioxide as a dispersant, the dispersant itself has high heat resistance, unlike a high molecular surfactant of a polyacrylate system having low heat resistance, and therefore, the heat resistance that the polyimide in the target polyimide microparticles can originally exhibit is not reduced. Furthermore, if at least one selected from the group consisting of a compound having a siloxane bond and silicon dioxide is used as a dispersant, a good emulsion can be obtained even if the amount of the dispersant is small, and a chemical imidization reaction of forming polyimide microparticles from polyamic acid microparticles can be performed in a system with a high concentration, and the manufacturing efficiency is excellent.
[0086] The compound having a siloxane bond is a compound having a Si—O—Si bond, and is preferably a compound having a structure represented by formula (1).
[0087]
[0088] In formula (1), R 1 , R 2 are the same or different and are each a hydrogen atom or an alkyl group. From the viewpoint of further demonstrating the effects of the present invention, the carbon number of the alkyl group is preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, particularly preferably 1 to 2, and most preferably 1. In formula (1), from the viewpoint of further demonstrating the effects of the present invention, R 1 , R 2 Preferably, they are all alkyl groups, and more preferably, they are methyl groups.
[0089] The compound having a siloxane bond is more preferably a compound having a polysiloxane structure having a structure represented by formula (1) as a repeating unit, and further preferably a compound having a structure represented by formula (1) (wherein R 1 Methyl, R 2 A compound having a polysiloxane structure (polydimethylsiloxane structure) in which a methyl group is a repeating unit.
[0090] One embodiment of the compound having a siloxane bond is polysiloxane. By using polysiloxane, the effect of the present invention can be further reflected. As a preferred embodiment of polysiloxane, a self-emulsified product of high-polymerization polysiloxane can be cited, and as a commercial product, for example, "KM-9787" made by Shin-Etsu Chemical Co., Ltd. can be cited.
[0091] Another embodiment of the compound having a siloxane bond is a compound having a structure represented by formula (1), which is a compound (A) having an azo group (-N=N-). By using such a compound (A), the effects of the present invention can be further exhibited.
[0092] From the viewpoint of further exhibiting the effects of the present invention, the number average molecular weight Mn of compound (A) is preferably 5,000 to 1,000,000, more preferably 10,000 to 800,000, further preferably 30,000 to 500,000, particularly preferably 40,000 to 300,000, and most preferably 50,000 to 200,000.
[0093] Compound (A) preferably has an amide bond (-NH-CO-) from the viewpoint of further demonstrating the effects of the present invention. By having an amide bond in addition to an azo group (-N=N-), the effects of the present invention can be further demonstrated due to electronic effects and steric effects derived from the azo group and the amide group.
[0094] As compound (A), it is more preferable to have a cyano group from the viewpoint of further demonstrating the effect of the present invention. By having an amide bond and a cyano group in addition to an azo group (-N=N-), the effect of the present invention can be further demonstrated by the electronic effect and stereo effect derived from the azo group, amide group and cyano group.
[0095] As compound (A), from the viewpoint of being able to further embody the effect of the present invention, it is a compound having a polydimethylsiloxane structure, an azo group, an amide group and a cyano group. As such a compound, any appropriate compound can be used within the scope of not damaging the effect of the present invention. As such a compound, specifically, for example, the trade names "VPS-1001" and "VPS-1001N" made by FUJIFILM Wako Pure Chemical Corporation, which are known as high molecular azo polymerization initiators containing polydimethylsiloxane units, can be cited.
[0096] One embodiment of the silicon dioxide is compound (B) having a specific surface area of 10 m 2 By using such a compound (B), the effect of the present invention can be further exhibited.
[0097] From the viewpoint of further demonstrating the effect of the present invention, the specific surface area of the compound (B) is preferably 10 m 2 / g~1000m 2 / g, more preferably 30m 2 / g~500m 2 / g, more preferably 50m 2 / g~300m 2 / g.
[0098] As compound (B), any compound having a specific surface area of 10 m 2 / g or more of hydrophobic silica particles, and any appropriate compound can be used within the range that does not impair the effect of the present invention. As such a compound, specifically, for example, trade names "AEROSIL R972", "AEROSIL R972CF", "AEROSIL R972V", "AEROSIL R974", "AEROSIL R976", "AEROSIL R976S", and "AEROSILR9200" manufactured by NIPPON AEROSIL CO., LTD. can be cited.
[0099] As the hydrocarbon solvent, any appropriate hydrocarbon solvent can be used within the range that does not impair the effect of the present invention. Such hydrocarbon solvents may be only one kind or two or more kinds. Such hydrocarbon solvents include, for example, pentane, hexane, cyclohexane, heptane, octane, benzene, toluene, xylene, and ethylbenzene.
[0100] The external oil phase may contain any other appropriate components as long as it contains at least one selected from the group consisting of a compound having a siloxane bond and silica and a hydrocarbon solvent, within the range that does not impair the effect of the present invention. From the viewpoint of further reflecting the effect of the present invention, the total content ratio of at least one selected from the group consisting of a compound having a siloxane bond and silica and the hydrocarbon solvent in the external oil phase is preferably 80% by weight to 100% by weight, more preferably 90% by weight to 100% by weight, further preferably 95% by weight to 100% by weight, particularly preferably 98% by weight to 100% by weight, and most preferably substantially 100% by weight. It should be noted that "substantially 100% by weight" means that although there are no other components intentionally mixed, it may contain extremely trace amounts (e.g., less than 1% by weight) of impurities that do not affect the effect of the present invention.
[0101] From the viewpoint of further exhibiting the effects of the present invention, the external oil phase is preferably prepared by dissolving at least one selected from the group consisting of compounds having a siloxane bond and silica in a hydrocarbon solvent.
[0102] The concentration of at least one selected from the group consisting of a compound having a siloxane bond and silicon dioxide in the external oil phase may be any appropriate concentration within a range that does not impair the effects of the present invention. From the viewpoint of further embodying the effects of the present invention, such a concentration is preferably 0.001% by weight to 10% by weight, more preferably 0.005% by weight to 5.0% by weight, and still more preferably 0.01% by weight to 3.0% by weight.
[0103] 《1-3. Process III》
[0104] In step III, a chemical imidization reaction is carried out in an emulsion prepared from the inner oil phase prepared in step I and the outer oil phase prepared in step II.
[0105] In step III, it is preferred that an emulsion is prepared from the inner oil phase and the outer oil phase, and a chemical imidization agent is added to the emulsion to carry out a chemical imidization reaction.
[0106] The mixing of the inner oil phase and the outer oil phase typically involves adding the inner oil phase to the outer oil phase.
[0107] Regarding the mixing ratio of the inner oil phase to the outer oil phase, from the viewpoint of further demonstrating the effects of the present invention, the weight ratio of the inner oil phase:the outer oil phase is preferably 1:10 to 1:500, more preferably 1:30 to 1:300, and even more preferably 1:50 to 1:100.
[0108] As a method for preparing an emulsion from the inner oil phase and the outer oil phase, any appropriate method may be adopted within the scope that does not impair the effect of the present invention. From the viewpoint of further embodying the effect of the present invention, as a method for preparing an emulsion from the inner oil phase and the outer oil phase, it is preferred to add the inner oil phase to the outer oil phase and emulsify it using an emulsifier or a disperser. Examples of the emulsifier and disperser include batch emulsifiers such as a homogenizer (manufactured by IKA Corporation, etc.), a Polytron homogenizer (manufactured by Central Scientific Commerce, Inc., Kinematica AG, etc.), and a homomixer MARKII (manufactured by PRIMIX Corporation); continuous emulsifiers such as an Ebara Milder (manufactured by EBARA CORPORATION), a FILMICS (manufactured by PRIMIX Corporation), a colloid mill (manufactured by Shinko Pantech Co., Ltd., etc.), a Slusher (manufactured by Mitsui Miike Kakoki Co., Ltd., etc.), a triangular wet micro-pulverizer (manufactured by Mitsui Miike Kakoki Co., Ltd., etc.), a Cavitron (manufactured by EUROTECH, etc.), and a fine flow mill (manufactured by Pacific Machinery & Engineering Co., Ltd.); and microfluidizers (manufactured by Powrex Corporation), a Nanomizer (manufactured by Nanomizer Inc.), and a Nanovater (manufactured by YOSHIDA High-pressure emulsifiers include high-pressure emulsifiers such as KIKAICO., LTD. and APV Gaulin (manufactured by Gaulin); membrane emulsifiers such as membrane emulsifiers (manufactured by REICA Co., Ltd., etc.); vibration emulsifiers such as VIBRO MIXER (manufactured by REICA Co., Ltd., etc.); ultrasonic emulsifiers such as ultrasonic homogenizers (manufactured by Branson, etc.).
[0109] When preparing the emulsion from the inner oil phase and the outer oil phase, any appropriate other components may be added within a range that does not impair the effects of the present invention.
[0110] The concentration of the polyamic acid microparticles in the emulsion prepared from the inner oil phase and the outer oil phase can be any appropriate concentration within the range that does not impair the effect of the present invention. From the viewpoint of further embodying the effect of the present invention, the concentration of the polyamic acid microparticles in the emulsion prepared from the inner oil phase and the outer oil phase is preferably 0.1% by weight or more, more preferably 0.15% by weight to 5.0% by weight, and further preferably 0.2% by weight to 1.0% by weight.
[0111] As a chemical imidizing agent, any appropriate chemical imidizing agent can be used within the range that does not impair the effect of the present invention. The chemical imidizing agent may be only one kind or two or more kinds. As such a chemical imidizing agent, for example, the combined use of pyridine and acetic anhydride can be cited. For the usage ratio in the combined use of pyridine and acetic anhydride, from the viewpoint of further reflecting the effect of the present invention, in terms of weight ratio, pyridine: acetic anhydride is preferably 1: 0.1 to 1: 10, more preferably 1: 0.3 to 1: 3, further preferably 1: 0.5 to 1: 2, and particularly preferably 1: 0.8 to 1: 1.2.
[0112] The amount of the chemical imidizing agent can be any appropriate amount within the range that does not impair the effect of the present invention. From the viewpoint of further embodying the effect of the present invention, the amount of the chemical imidizing agent is preferably 50 to 1200 parts by weight, more preferably 100 to 800 parts by weight, relative to 100 parts by weight of the polyamic acid microparticles in the internal oil phase.
[0113] The reaction temperature of the chemical imidization reaction can be set to any appropriate temperature within the range that does not impair the effect of the present invention, depending on the boiling point of the hydrocarbon solvent in the external oil phase. From the viewpoint of further demonstrating the effect of the present invention, the reaction temperature of the chemical imidization reaction is preferably 100° C. or less, more preferably 0° C. to 90° C., and more preferably 20° C. to 80° C.
[0114] Any appropriate time may be adopted as the reaction time of the chemical imidization reaction within the range that does not impair the effects of the present invention. From the viewpoint of further demonstrating the effects of the present invention, the reaction time of the chemical imidization reaction is preferably 0.1 to 50 hours, more preferably 1.0 to 24 hours.
[0115] The chemical imidization reaction forms polyimide hollow particles in the reaction solution. The obtained polyimide hollow particles can be separated by solid-liquid separation by any appropriate method, washed by any appropriate method as needed, and dried by any appropriate method as needed.
[0116] As a method for solid-liquid separation, any appropriate method can be adopted within a range that does not impair the effects of the present invention. As such a method for solid-liquid separation, for example, centrifugal separation can be mentioned.
[0117] 《《2. Polyimide Hollow Particles》》
[0118] The hollow polyimide particles according to the embodiment of the present invention have a shell and a hollow portion surrounded by the shell. It should be noted that, as mentioned above, the so-called hollow in the present invention refers to a state in which the interior is filled with substances other than resin, such as gas, liquid, etc., and in terms of further embodying the effect of the present invention, it is preferably a state filled with gas. In addition, as mentioned above, the shell and the hollow portion surrounded by the shell can be formed by one hollow region, or by multiple hollow regions (porous structure).
[0119] The volume average particle size of the polyimide hollow particles based on the embodiment of the present invention is preferably 0.1 μm to 100 μm, more preferably 0.5 μm to 80 μm, and further preferably 1.0 μm to 50 μm. When the volume average particle size of the polyimide hollow particles based on the embodiment of the present invention deviates from the above range and is too small, the thickness of the shell portion becomes relatively thinner, and therefore, there is a concern that the polyimide hollow particles will not have sufficient strength. When the average particle size of the polyimide hollow particles based on the embodiment of the present invention deviates from the above range and is too large, there is a concern that the chemical imidization reaction is not sufficiently carried out and the heat resistance is reduced.
[0120] For the polyimide hollow particles based on the embodiment of the present invention, the coefficient of variation (CV value) of the particle size is preferably less than 80%, more preferably 1% to 80%, further preferably 2% to 75%, particularly preferably 3% to 70%, and most preferably 5% to 65%. If the coefficient of variation (CV value) of the particle size of the polyimide hollow particles based on the embodiment of the present invention is within the above range, the effect of the present invention can be better reflected. When the coefficient of variation (CV value) of the particle size of the polyimide hollow particles based on the embodiment of the present invention deviates from the above range and is too large, due to the increase in the number of coarse particles, for example, when the resin layer is formed by a resin composition, there is a concern that the film will become difficult and the thickness will fluctuate. The smaller the coefficient of variation (CV value) of the particle size of the polyimide hollow particles based on the embodiment of the present invention, the more consistent the particle size, so it is preferred, but if considering the aspects that can be made in reality, the lower limit value can be as described above.
[0121] The 5% thermal weight loss temperature of the polyimide hollow particles based on the embodiment of the present invention when heated at 10°C / min in an air atmosphere is preferably 330°C or more, more preferably 350°C or more, further preferably 370°C or more, and particularly preferably 400°C or more. The upper limit of the above 5% weight loss temperature is preferably 600°C or less in practice. As long as the above 5% thermal weight loss temperature is within the above range, the polyimide hollow particles based on the embodiment of the present invention can exhibit excellent heat resistance. If the above 5% thermal weight loss temperature deviates from the above range and is too small, for example, when the polyimide hollow particles are mixed with a thermosetting resin, due to the heating used for the curing reaction, the polyimide hollow particles will be deformed and lose the hollow part, thereby, there is a concern about reducing the low dielectric effect and the low dielectric loss tangent effect.
[0122] For the polyimide hollow particles based on the embodiment of the present invention, when the relative dielectric constant of the film F1 formed by mixing 20 parts by weight of the polyimide hollow particles and 80 parts by weight of polyimide is set to Dk1, and the relative dielectric constant of the film F0 formed only by polyimide is set to Dk0, the relative dielectric constant reduction rate calculated by (Dk1 / Dk0)×100(%) is preferably 10% or more, more preferably 15% or more, further preferably 18% or more, and particularly preferably 20% or more. The upper limit of the above-mentioned relative dielectric constant reduction rate is preferably 50% or less in practice. If the above-mentioned relative dielectric constant reduction rate is within the above-mentioned range, the relative dielectric constant of the polyimide hollow particles based on the embodiment of the present invention is low, and therefore, when added to a resin, for example, an excellent low dielectric effect can be achieved.
[0123] For the polyimide hollow particles based on the embodiment of the present invention, when the dielectric loss tangent of the film F1 formed by mixing 20 parts by weight of the polyimide hollow particles with 80 parts by weight of polyimide is set to Df1, and the dielectric loss tangent of the film F0 formed only by polyimide is set to Df0, the dielectric loss tangent reduction rate calculated by (Df1 / Df0)×100(%) is preferably 4% or more, more preferably 7% or more, further preferably 10% or more, and particularly preferably 12% or more. The upper limit of the above-mentioned dielectric loss tangent reduction rate is preferably 50% or less in practice. If the above-mentioned dielectric loss tangent reduction rate is within the above-mentioned range, the dielectric loss tangent of the polyimide hollow particles based on the embodiment of the present invention is low, so that, for example, when added to a resin, an excellent low dielectric loss tangent effect can be achieved.
[0124] The hollow polyimide particles according to the embodiment of the present invention are preferably obtained by the method for producing hollow polyimide particles according to the embodiment of the present invention.
[0125] 《《3. Application of polyimide hollow particles》》
[0126] The polyimide hollow particles based on the embodiments of the present invention can be used for various purposes. In terms of being able to make better use of the effects of the present invention, the polyimide hollow particles based on the embodiments of the present invention can be applied to semiconductor components (representatively, resin compositions for semiconductor components), coating compositions, cosmetics, paper-covered compositions, heat-insulating compositions, light-diffusing compositions, light-diffusing films and the like, and are particularly suitable for resin compositions for semiconductor components and coating compositions.
[0127] 《3-1. Resin composition for semiconductor components》
[0128] The hollow polyimide particles according to the embodiment of the present invention can achieve low dielectric constant and low dielectric loss tangent and can exhibit excellent heat resistance, and therefore can be suitably used in a resin composition for a semiconductor member.
[0129] The resin composition for semiconductor components according to the embodiment of the present invention includes hollow resin particles according to the embodiment of the present invention.
[0130] The semiconductor component refers to a component constituting a semiconductor, and examples thereof include a semiconductor package and a semiconductor module. In the present specification, the resin composition for a semiconductor component refers to a resin composition used in a semiconductor component.
[0131] A semiconductor package refers to a package that has an IC chip as an essential component and is constructed using at least one component selected from a molding resin, an underfill material, a molded underfill material, a chip bonding material, a prepreg for a semiconductor package substrate, a metal-clad laminate for a semiconductor package substrate, and a laminate material for a printed circuit board for a semiconductor package.
[0132] A semiconductor module refers to a module that has a semiconductor package as an essential component and is constructed using at least one component selected from a prepreg for a printed circuit board, a metal-clad laminate for a printed circuit board, a build-up material for a printed circuit board, a solder resist material, a cover film, an electromagnetic wave shielding film, and an adhesive sheet for a printed circuit board.
[0133] 《3-2. Coating composition》
[0134] The polyimide hollow particles according to the embodiment of the present invention can impart excellent appearance to a coating film including the hollow polyimide particles, and therefore can be suitably used in a coating composition.
[0135] The coating composition according to the embodiment of the present invention includes the polyimide hollow particles according to the embodiment of the present invention.
[0136] The coating composition according to the embodiment of the present invention preferably comprises at least one selected from a binder resin and a UV curable resin. The binder resin may be only one, or two or more. The UV curable resin may be only one, or two or more.
[0137] As the binder resin, any appropriate binder resin can be used within the range that does not impair the effect of the present invention. As such a binder resin, for example, a resin soluble in an organic solvent or water, and an emulsion-type aqueous resin dispersible in water can be cited. As the binder resin, specifically, for example, acrylic resins, alkyd resins, polyester resins, polyurethane resins, chlorinated polyolefin resins, and amorphous polyolefin resins can be cited.
[0138] As the UV curable resin, any appropriate UV curable resin can be used within the range that does not impair the effect of the present invention. As such UV curable resin, for example, multifunctional (meth)acrylate resins and multifunctional urethane acrylate resins can be cited, preferably multifunctional (meth)acrylate resins, more preferably multifunctional (meth)acrylate resins having three or more (meth)acryloyl groups in one molecule. Specific examples of the polyfunctional (meth)acrylate resin having three or more (meth)acryloyl groups in one molecule include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, triglycerol pentaacrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol triacrylate, and tripentaerythritol hexaacrylate.
[0139] When the coating composition according to the embodiment of the present invention includes at least one selected from a binder resin and a UV curable resin, the content ratio can be any appropriate content ratio according to the purpose. Representatively, the hollow resin particles according to the embodiment of the present invention are preferably 5% by weight to 50% by weight, more preferably 10% by weight to 50% by weight, and further preferably 20% by weight to 40% by weight, relative to the total amount of at least one selected from a binder resin (in the case of an emulsion-type aqueous resin, solid content conversion) and a UV curable resin and the hollow resin particles according to the embodiment of the present invention.
[0140] When a UV curable resin is used, it is preferred to use a photopolymerization initiator in combination. As a photopolymerization initiator, any appropriate photopolymerization initiator can be used within the scope of not damaging the effect of the present invention. As such a photopolymerization initiator, for example: acetophenones, benzoins, benzophenones, phosphine oxides, ketals, α-hydroxyalkyl phenones, α-aminoalkyl phenones, anthraquinones, thioxanthones, azo compounds, peroxides (described in Japanese Patent Publication No. 2001-139663, etc.), 2,3-dialkyl dione compounds, disulfide compounds, fluoroamine compounds, aromatic sulfoniums, onium salts, borates, active halogen compounds, α-acyl oxime esters can be cited.
[0141] The coating composition according to the embodiment of the present invention may contain a solvent. The solvent may be only one kind or two or more kinds. When the coating composition according to the embodiment of the present invention contains a solvent, the content ratio thereof may adopt any appropriate content ratio according to the purpose.
[0142] As the solvent, any appropriate solvent can be used within the scope that does not impair the effect of the present invention. As such a solvent, a solvent that can dissolve or disperse the binder resin or UV curable resin is preferred. As such a solvent, if it is an oil-based paint, for example, hydrocarbon solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as dioxane, ethylene glycol diethyl ether, and ethylene glycol monobutyl ether can be cited. If it is a water-based paint, for example, water and alcohols can be cited.
[0143] The coating composition of the embodiment of the present invention can be diluted as needed to adjust the viscosity. As a diluent, any appropriate diluent can be used according to the purpose. As such a diluent, the aforementioned solvent can be cited. The diluent can be only one, or it can be two or more.
[0144] The coating composition according to the embodiment of the present invention may contain other components as needed, such as a coating surface conditioner, a fluidity conditioner, a UV absorber, a light stabilizer, a curing catalyst, an extender pigment, a coloring pigment, a metallic pigment, a mica powder pigment, and a dye.
[0145] When using the coating composition based on the embodiment of the present invention to form a coating film, as its coating method, any appropriate coating method can be adopted according to the purpose. As such coating method, for example: spray coating method, roller coating method, brush coating method, coating reverse roll coating method, gravure coating method, die coating method, comma coating method, spray coating method can be enumerated.
[0146] When a coating film is formed using a coating composition based on an embodiment of the present invention, as its formation method, any appropriate formation method can be adopted according to the purpose. As such a formation method, for example, the following method can be cited: any coating surface applied to a substrate makes a coating film, and after the coating film is dried, the coating film is solidified as required to form a coating film. As a substrate, for example, metal, wood, glass, plastic (PET (polyethylene terephthalate), PC (polycarbonate), acrylic resin, TAC (triacetyl cellulose) etc.) can be cited.
[0147] Example
[0148] The present invention will be specifically described below with reference to Examples, but the present invention is not limited to these Examples. It should be noted that, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".
[0149] 《Determination of volume average particle size and coefficient of variation》
[0150] The volume average particle size of the particles was measured according to the Coulter method as described below.
[0151] The volume average particle size of the particles is measured by Coulter Multisizer (registered trademark) 3 (measurement device manufactured by Beckman Coulter, Inc.). The measurement is carried out using an aperture calibrated according to the Multisizer (registered trademark) 3 user manual published by Beckman Coulter, Inc. It should be noted that the aperture used in the measurement is appropriately selected according to the size of the particles to be measured: when the assumed volume average particle size of the particles to be measured is 1 μm or more and 10 μm or less, an aperture with a size of 50 μm is selected, when the assumed volume average particle size of the particles to be measured is greater than 10 μm and less than 30 μm, an aperture with a size of 100 μm is selected, when the assumed volume average particle size of the particles is greater than 30 μm and less than 90 μm, an aperture with a size of 280 μm is selected, when the assumed volume average particle size of the particles is greater than 90 μm and less than 150 μm, an aperture with a size of 400 μm is selected, etc. If the measured volume average particle size is different from the assumed volume average particle size, change to an aperture of appropriate size and measure again. Current (aperture current) and Gain (gain) are appropriately set according to the size of the selected aperture. For example, when selecting an aperture with a size of 50 μm, set Current (aperture current) to -800 and Gain (gain) to 4. When selecting an aperture with a size of 100 μm, set Current (aperture current) to -1600 and Gain (gain) to 2. When selecting an aperture with a size of 280 μm and 400 μm, set Current (aperture current) to -3200 and Gain (gain) to 1.
[0152] Using a touch mixer (manufactured by Yamato Scientific Co., Ltd., "TOUCHMIXER MT-31") and an ultrasonic cleaner (manufactured by VELVO-CLEAR, "ULTRASONIC CLEANER VS-150"), 0.1 g of particles were dispersed in 10 ml of a 0.1 wt% nonionic surfactant aqueous solution to form a dispersion, which was used as a sample for measurement. During the measurement, the beaker was slowly stirred to such an extent that bubbles did not enter, and the measurement was terminated when 100,000 particles were measured. It should be noted that the volume average particle size of the particles is the arithmetic mean in the volume-based particle size distribution of 100,000 particles.
[0153] The coefficient of variation (CV value) of the particle size of the particles was calculated according to the following mathematical formula.
[0154] Coefficient of variation of particle size (CV value) (%) = (standard deviation of particle size distribution based on volume of particles / volume average particle size of particles) × 100 (%)
[0155] 《Cross-Section Observation》
[0156] The dried particles were mixed with a photocurable resin "D-800" (manufactured by JEOL Ltd.) and irradiated with ultraviolet light to obtain a cured product. After that, the cured product was cut with pliers, the cross section was processed to be smooth with a cutter, and the sample was coated with a sputtering device "Auto Fine Coater JFC-1300" manufactured by JEOL Ltd. Next, the cross section of the sample was photographed with a secondary electron detector of a scanning electron microscope "SU1510" manufactured by Hitachi High-Technologies Corporation.
[0157] 《Determination of 5% weight loss temperature when heating at 10°C / min in air atmosphere》
[0158] The 5% thermal weight loss temperature was measured using a differential thermal-thermogravimetric simultaneous measuring apparatus "NEXTASTA200RV" manufactured by Hitachi High-Tech Science Corporation. The sampling method and temperature conditions were as follows.
[0159] Fill the bottom of the platinum measuring container with a sample of 10.5±0.5 mg in a gapless manner as a sample for measurement. Measure the 5% thermal weight loss temperature with alumina as the reference substance at an air gas flow rate of 200 mL / min. The TG / DTA curve is obtained by heating the sample from 30°C to 800°C at a heating rate of 10°C / min. From the obtained curve, the temperature at which 5% weight loss occurs is calculated using the analytical software attached to the device as the 5% thermal weight loss temperature.
[0160] [Production Example 1]: Synthesis of polyamic acid microparticles A
[0161] 0.64 g of 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA) was dissolved in 39.4 g of acetone as a first solution, and 0.40 g of 4,4′-diaminodiphenyl ether (DPE) was dissolved in 39.4 g of acetone as a second solution to prepare respective solutions.
[0162] Next, the two solutions were mixed at 25° C. and irradiated in an ultrasonic homogenizer for 5 minutes to react to precipitate polyamic acid microparticles. Thereafter, solid-liquid separation was performed in a centrifuge, and the mixture was washed several times with acetone and dried to obtain polyamic acid microparticles A.
[0163] The obtained particles were observed with a scanning electron microscope and confirmed to be monodispersed spherical particles.
[0164] [Production Example 2]: Synthesis of polyamic acid microparticles B
[0165] After preparing the first solution and the second solution in the same manner as in Production Example 1, 5 g of ion exchange water was mixed in the first solution and stirred at 25° C. for 30 minutes. Next, the two solutions were mixed at 25° C. and stirred for 10 minutes to react, thereby precipitating polyamic acid microparticles. Thereafter, solid-liquid separation was performed using a centrifuge, and a washing process was performed several times using acetone, and then dried to obtain polyamic acid microparticles B.
[0166] The obtained particles were observed with a scanning electron microscope and confirmed to be monodispersed spherical particles.
[0167] [Example 1]
[0168] 0.2 g of the polyamic acid fine particles A obtained in Production Example 1 and 0.8 g of N,N-dimethylformamide (DMF) as a solvent were mixed and dissolved to prepare an internal oil phase.
[0169] Separately, 0.56 g of azo group-containing polydimethylsiloxane (trade name "VPS-1001", manufactured by FUJIFILM Wako Pure Chemical Corporation) and 56 g of hexane as a solvent were mixed and dissolved to prepare an external oil phase.
[0170] The inner oil phase was added to the outer oil phase, and an emulsification / dispersion treatment was performed at 3000 rpm for 2 minutes using a Polytron homogenizer PT10-35 (manufactured by Central Scientific Commerce, Inc.). 0.4 g of acetic anhydride / 0.4 g of pyridine as a chemical imidization agent was added to the obtained emulsion, and the mixture was heated at 60° C. for 3 hours while stirring to allow the chemical imidization reaction to proceed. Thereafter, the reaction system was cooled to room temperature, and after the reaction was completed, the total amount of the obtained slurry was passed through a JIS test sieve (aperture: 33 μm) (JIS standard number: Z 8801-1: 2019) to remove coarse particles, and then the particles were centrifuged to settle, and the supernatant was removed, and the particles were washed with cyclohexane and 2-propanol, and dried to obtain polyimide hollow particles (1).
[0171] The volume average particle size of the obtained polyimide hollow particles (1) was 20.7 μm. The particle cross section of the obtained polyimide hollow particles (1) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0172] The results are shown in Table 1.
[0173] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particles (1) is shown in Figure 1 .
[0174] [Example 2]
[0175] Polyimide hollow particles (2) were obtained in the same manner as in Example 1 except that the solvent of the external oil phase was changed to 66.4 g of cyclohexane.
[0176] The volume average particle size of the obtained polyimide hollow particles (2) was 19.9 μm. The particle cross section of the obtained polyimide hollow particles (2) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0177] The results are shown in Table 1.
[0178] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particles (2) is shown in Figure 2 .
[0179] [Example 3]
[0180] Hydrophobic silica particles (trade name "AEROSIL (registered trademark) R972", specific surface area = 110 ± 20 m 2 / g, NIPPON AEROSIL CO., LTD.): 0.04 g) was used instead of 0.56 g of azo group-containing polydimethylsiloxane (trade name “VPS-1001”, manufactured by FUJIFILM Wako Pure Chemical Corporation), and polyimide hollow particles (3) were obtained in the same manner as in Example 2.
[0181] The volume average particle size of the obtained polyimide hollow particles (3) was 19.2 μm. The particle cross section of the obtained polyimide hollow particles (3) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0182] The results are shown in Table 1.
[0183] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (3) is shown in Figure 3 .
[0184] [Example 4]
[0185] Polyimide hollow particles (4) were obtained in the same manner as in Example 3 except that dimethylacetamide was used as the solvent of the inner oil phase.
[0186] The volume average particle size of the obtained polyimide hollow particles (4) was 16.3 μm. The particle cross section of the obtained polyimide hollow particles (4) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0187] The results are shown in Table 1.
[0188] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (4) is shown in Figure 4 .
[0189] [Example 5]
[0190] Polyimide hollow particles (5) were obtained in the same manner as in Example 3 except that the solvent of the inner oil phase was changed to N-methyl-2-pyrrolidone.
[0191] The volume average particle size of the obtained polyimide hollow particles (5) was 14.9 μm. The particle cross section of the obtained polyimide hollow particles (5) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0192] The results are shown in Table 1.
[0193] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (5) is shown in Figure 5 .
[0194] [Example 6]
[0195] Polyimide hollow particles (6) were obtained in the same manner as in Example 3 except that the reaction conditions after adding the chemical imidizing agent were changed to heating at 70° C. for 1 hour with stirring.
[0196] The volume average particle size of the obtained polyimide hollow particles (6) was 14.0 μm. The particle cross section of the obtained polyimide hollow particles (6) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0197] The results are shown in Table 1.
[0198] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (6) is shown in Figure 6 .
[0199] [Example 7]
[0200] Polyimide hollow particles (7) were obtained in the same manner as in Example 3 except that the polyamic acid fine particles to be used were the polyamic acid fine particles B obtained in Production Example 2.
[0201] The volume average particle size of the obtained polyimide hollow particles (7) was 14.6 μm. The particle cross section of the obtained polyimide hollow particles (7) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0202] The results are shown in Table 1.
[0203] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (7) is shown in Figure 7 .
[0204] [Example 8]
[0205] Polysiloxane (trade name "KM-9787", manufactured by Shin-Etsu Chemical Co., Ltd.): 0.56 g was used instead of hydrophobic silica particles (trade name "AEROSIL (registered trademark) R972", specific surface area = 110 ± 20 m 2 / g, NIPPONAEROSIL CO., LTD.): 0.04 g, the same procedure as in Example 3 was carried out to obtain polyimide hollow particles (8).
[0206] The volume average particle size of the obtained polyimide hollow particles (8) was 21.2 μm. The particle cross section of the obtained polyimide hollow particles (8) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0207] The results are shown in Table 1.
[0208] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (8) is shown in Figure 8 .
[0209] [Example 9]
[0210] Polyimide hollow particles (9) were obtained in the same manner as in Example 8, except that the polyamic acid fine particles to be used were the polyamic acid fine particles B obtained in Production Example 2.
[0211] The volume average particle size of the obtained polyimide hollow particles (9) was 19.2 μm. The particle cross section of the obtained polyimide hollow particles (9) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0212] The results are shown in Table 1.
[0213] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (9) is shown in Fig. 9 .
[0214] [Example 10]
[0215] Polyimide hollow particles (10) were obtained in the same manner as in Example 2 except that 0.1 g of polyamic acid microparticles B obtained in Production Example 2, 0.01 g of polybutyl methacrylate (PBMA) (Mw=100000) as another non-crosslinked polymer, and 0.9 g of N,N-dimethylformamide (DMF) as a solvent were mixed and dissolved to prepare an internal oil phase.
[0216] The volume average particle size of the obtained polyimide hollow particles (10) was 15.3 μm. The particle cross section of the obtained polyimide hollow particles (10) was observed using a scanning electron microscope, and the presence of a hollow structure having one or more void regions covered with a shell was confirmed.
[0217] The results are shown in Table 1.
[0218] A scanning electron micrograph of a particle cross section of the obtained polyimide hollow particle (10) is shown in Fig.10 .
[0219] [Comparative Example 1]
[0220] The emulsification / dispersion treatment was carried out in the same manner as in Example 1 except that 0.56 g of an acrylic resin (trade name "Macromonomer AB-6", manufactured by Toagosei Co., Ltd.) was used instead of 0.56 g of an azo group-containing polydimethylsiloxane (trade name "VPS-1001", manufactured by FUJIFILM Wako Pure Chemical Corporation). However, the emulsification stability was extremely low, coalescence of oil droplets occurred, and an emulsion could not be obtained.
[0221] [Comparative Example 2]
[0222] The emulsification / dispersion treatment was carried out in the same manner as in Comparative Example 1, except that the polyamic acid fine particles used were the polyamic acid fine particles B obtained in Production Example 2. However, the emulsification stability was extremely low, and coalescence of oil droplets occurred, so that an emulsion could not be obtained.
[0223] [Table 1]
[0224]
[0225] 《Performance evaluation: Evaluation of relative dielectric constant / dielectric loss tangent》
[0226] 0.425 g of polyimide hollow particles were collected, and 8.3 g of ethyl acetate and 1.7 g of solvent-soluble polyimide KPI-MX300F (manufactured by Kawamura Sangyo Co., Ltd.) were deaerated and stirred using a planetary stirring degassing machine ("Mazerustar KK-250" manufactured by KURABO INDUSTRIES LTD.) to prepare a resin composition.
[0227] The resin composition was applied to a glass plate having a thickness of 5 mm using an applicator with a wet thickness setting of 250 μm, and then heated at 60° C. for 30 minutes, at 90° C. for 10 minutes, at 150° C. for 30 minutes, and at 200° C. for 30 minutes to remove ethyl acetate, and then cooled to room temperature to obtain a film containing polyimide hollow particles. The relative dielectric constant / dielectric loss tangent of the obtained film was evaluated by a cavity resonance method (measurement frequency: 10 GHz).
[0228] In addition, the relative dielectric constant / dielectric loss tangent of a film not containing polyimide hollow particles (a film composed only of polyimide) was evaluated in the same manner.
[0229] When the relative dielectric constant of the film containing polyimide hollow particles obtained above is set to Dk1 and the relative dielectric loss tangent is set to Df1, and when the relative dielectric constant of the film formed only by polyimide is set to Dk0 and the relative dielectric loss tangent is set to Df0, the reduction rate of the relative dielectric constant calculated by (Dk1 / Dk0)×100(%) and the reduction rate of the dielectric loss tangent calculated by (Df1 / Df0)×100(%) are calculated.
[0230] The polyimide hollow particles (2), (3), and (7) obtained in Examples 2, 3, and 7 were evaluated.
[0231] The results are shown in Table 2.
[0232] [Table 2]
[0233] Polyimide Hollow Particles (2) (3) (7) film (2) (3) (7) Relative dielectric constant reduction rate (%) 20.6 23.3 23.5 Dielectric loss tangent reduction rate (%) 13.7 7.4 4.2
[0234] From this result, it can be confirmed that the hollow polyimide particles provided by the present invention have an effect of reducing the relative dielectric constant / dielectric loss tangent of the substrate, and are effective for achieving a lower dielectric constant and a lower dielectric loss tangent of a semiconductor material.
[0235] Industrial Applicability
[0236] The polyimide hollow particles based on the embodiments of the present invention can be used for various purposes. In terms of being able to make better use of the effects of the present invention, the polyimide hollow particles based on the embodiments of the present invention can be applied to semiconductor components (representatively, resin compositions for semiconductor components), coating compositions, cosmetics, paper-covered compositions, heat-insulating compositions, light-diffusing compositions, light-diffusing films and the like, and are particularly suitable for resin compositions for semiconductor components and coating compositions.
Claims
1. A method for producing polyimide hollow particles, comprising the steps of: A process for preparing an internal oil phase, wherein the internal oil phase comprises polyamic acid particles and a solvent; A step of preparing an external oil phase, wherein the external oil phase comprises at least one selected from the group consisting of a compound having a siloxane bond and silicon dioxide and a hydrocarbon solvent; and, A step of carrying out a chemical imidization reaction in an emulsion prepared from the inner oil phase and the outer oil phase.
2. The method for producing hollow polyimide particles according to claim 1, wherein: The compound having a siloxane bond is polysiloxane.
3. The method for producing hollow polyimide particles according to claim 1, wherein: The compound having a siloxane bond has an azo group.
4. The method for producing polyimide hollow particles according to claim 1, wherein: The silicon dioxide has a specific surface area of 10m 2 / g or more hydrophobic silica particles.
5. The method for producing polyimide hollow particles according to claim 1, wherein: The reaction temperature of the chemical imidization reaction is below 100°C.
6. The method for producing hollow polyimide particles according to claim 1, wherein: The solvent contained in the internal oil phase is an amide solvent.
7. The method for producing polyimide hollow particles according to claim 1, wherein: The concentration of the polyamic acid fine particles in the emulsion is 0.1% by weight or more.
8. A polyimide hollow particle comprising a shell portion and a hollow portion surrounded by the shell portion, The volume average particle size of the polyimide hollow particles is 0.1 μm to 100 μm.
9. The polyimide hollow particles according to claim 8, wherein The coefficient of variation (CV value) of the particle diameter of the polyimide hollow particles is 80% or less.
10. The polyimide hollow particles according to claim 8, wherein The polyimide hollow particles have a 5% thermal weight loss temperature of 330° C. or higher when the temperature is increased at 10° C. / min in an air atmosphere.
11. The polyimide hollow particles according to claim 8, wherein When the relative dielectric constant of the film F1 formed by mixing 20 parts by weight of the polyimide hollow particles and 80 parts by weight of polyimide is set to Dk1, and the relative dielectric constant of the film F0 formed only by polyimide is set to Dk0, the relative dielectric constant reduction rate calculated by (Dk1 / Dk0)×100(%) is greater than 20%. 12 . The polyimide hollow particles according to claim 8 , which are obtained by the production method according to claim 1 .
Citation Information
Patent Citations
JP1974091327A
Akurironitorirukeiseniganjuseramitsukusufukugoshoketsutai no seizoho
JP1976033107A
Console
JP1979029922A
Resin composition for optical shaping, its preparation process and optically shaped product
JP2001139663A
Hollow particles
JP2009235294A